Boosting Creative Thinking with the 8E Learning Cycle: An Experimental Study on Virus Concepts in Senior High School - Helmira, Merisca Revya; Haviz, M. (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Creative thinking skills are a crucial foundation for developing students' potential to become knowledgeable, competent, critical, and innovative individuals. This study aims to examine the effect of a project-based learning model using the 8E Learning Cycle on students' creative thinking skills in the topic of viruses at the senior high school (SMA) Phase E level. The research employed a true experimental design with a posttest-only control group. The study involved Grade X students of SMAN 1 Lareh Sago Halaban for the 2024/2025 academic year. Data were analyzed using an independent samples t-test with a significance level of ╬▒ = 0.05. The results showed a significance value of 0.000 < 0.05, indicating a significant difference between the experimental and control groups. The average creative thinking test score in the experimental class was 58.38% (categorized as fair), while the control class scored 36.15% (categorized as low). These findings demonstrate that the application of the 8E Learning Cycle-based project model significantly enhances studentsÔÇÖ creative thinking skills. Therefore, this model is effective in fostering creative thinking through contextual and project-oriented learning approaches.┬á